CaV3.2 calcium channels contribute to trigeminal neuralgia. Issue 12 (20th December 2022) - Gambeta, Eder; Gandini, Maria A.; Souza, Ivana A.; Zamponi, Gerald W.
Abstract : Supplemental Digital Content is Available in the Text. Cav3.2 T-type calcium channels are identified as potential therapeutic targets for facial pain. Abstract: Trigeminal neuralgia (TN) is a rare but debilitating disorder characterized by excruciating facial pain, with a higher incidence in women. Recent studies demonstrated that TN patients present mutations in the gene encoding the CaV 3.2 T-type calcium channel, an important player in peripheral pain pathways. We characterize the role of CaV 3.2 channels in TN at 2 levels. First, we examined the biophysical properties of CACNA1H variants found in TN patients. Second, we investigated the role of CaV 3.2 in an animal model of trigeminal neuropathic pain. Whole-cell patch-clamp recordings from 4 different mutants expressed in tsA-201 cells (E286K in the pore loop of domain I, H526Y, G563R, and P566T in the domain I-II linker) identified a loss of function in activation in the E286K mutation and gain of function in the G563R and P566T mutations. Moreover, a loss of function in inactivation was observed with the E286K and H526Y mutations. Cell surface biotinylation revealed no difference in channel trafficking among the variants. The G563R mutant also caused a gain of function in the firing properties of transfected trigeminal ganglion neurons. In female and male mice, constriction of the infraorbital nerve induced facial thermal heat hyperalgesia. Block of T-type channels with Z944 resulted in antihyperalgesia. The effect of Z944 was absent in CaV 3.2 −/− mice, indicating that CaV 3.2 is the molecular target of the antihyperalgesic Z944 effect. Finally, enzyme-linked immunosorbent assay analysis revealed increased CaV 3.2 channel expression in the spinal trigeminal subnucleus caudalis. Altogether, the present study demonstrates an important role of CaV 3.2 channels in trigeminal pain.